Research Progress, Trends, and Updates on STEM Learning-ESD: A Bibliometric Analysis - Suci Siti Lathifah; Ari Widodo; Ida Kaniawati; Siti Sriyati (Postgraduate, University of Mataram, 2024)
The aim of this paper is to analyse research trends and address knowledge gaps in order to improve STEM-ESD learning. Technical terms are explained upon first use, and sentence structure is clear and unambiguous. The bibliometric review examines current research progress, trends, and updates related to STEM-ESD learning. The study used the Scopus database to select documents and VOSviewer software to investigate bibliometrics. STEM-ESD research shows an upward trend based on the analysis of 19 collections of STEM and ESD learning papers from 2010 to 2023. Indonesia leads in conducting STEM-ESD research, with the highest number of publications on this theme in 2022. In 2010, the significance of STEM-ESD research was its application in the STEM curriculum. STEM-ESD research has facilitated the inclusion of various social science topics in the learning process. This fosters 21st-century skills in students through a project-based learning model. Further STEM-ESD research can be advanced by improving pedagogical design capacity, biodiversity, sustainable development goals, formal and initial teacher training, biology education, and sustainable learning. This will lead to more innovative research.